2018
DOI: 10.1186/s12889-018-5798-6
|View full text |Cite
|
Sign up to set email alerts
|

Household latrine utilization and its association with educational status of household heads in Ethiopia: a systematic review and meta-analysis

Abstract: BackgroundEthiopia has been experiencing a high prevalence of communicable diseases, which resulted in high morbidity, mortality, and hospital admission rates. One of the highest contributing factors for this is lower level of latrine utilization. There had been significantly varying finding reports with regard to the level of latrine utilization and its association with education level from different pocket studies in the country. Therefore, this systematic review and meta-analysis was aimed to estimate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
35
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 29 publications
11
35
3
Order By: Relevance
“…These findings are in line with findings from the study conducted in Ethiopia which revealed a strong association between the latrine type, utilization, and social characteristics/status of the household individuals. 14 The household survey data revealed further that the level of income and sanitation facility was insignificant which is contrary to other studies that showed a very strong association between participants' level of income and the type of latrine ownership. 1,15 However, low income as a barrier toward installation of improved sanitation facility emerged in all the FGDs.…”
Section: Discussioncontrasting
confidence: 72%
“…These findings are in line with findings from the study conducted in Ethiopia which revealed a strong association between the latrine type, utilization, and social characteristics/status of the household individuals. 14 The household survey data revealed further that the level of income and sanitation facility was insignificant which is contrary to other studies that showed a very strong association between participants' level of income and the type of latrine ownership. 1,15 However, low income as a barrier toward installation of improved sanitation facility emerged in all the FGDs.…”
Section: Discussioncontrasting
confidence: 72%
“…Regarding latrine utilization, it was higher than evidence from systematic reviews at the national level (37.7%), Central zone of Tigray, Northern Ethiopia (58.9%), Awabel district of Amhara region (52%), and Gulomekeda of Tigray region (57.3%) [8,9,19,28]. Latrine location inside the house compound was four times more likely utilized by household members (AOR � 4.463, 95% CI: 1.021-19.516).…”
Section: Discussionmentioning
confidence: 66%
“…However, a recent report showed that the practice of open defecation in Ethiopia is increasing in the same way it was rising in sub-Saharan African countries [ 3 , 10 ], and approximately 35.6% of the population engaged in open defecation. This means that Ethiopia is off-tracking from the achievement of the Sustainable Development Goal (SDG), where half of the population still relies on unimproved sanitation facilities and 50% latrine utilization [ 11 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%